Different effectiveness of acupuncture treatment schedule on ART pregnancy outcomes: a systematic review and network meta-analysis - Yang, Yunhong; Chen, Huan; Tang, Han; Kuang, Hongjun; Gou, Yi; Zhao, Hong (Frontiers in Endocrinology, 2025)
BackgroundAcupuncture shows potential in enhancing pregnancy outcomes in Assisted Reproductive Technology (ART), yet the variability in protocols necessitates identifying optimal strategies.ObjectiveThis study aimed to evaluate the effects of different acupuncture treatment schedules—specifically the timing, duration, and frequency—on ART pregnancy outcomes, and to identify the most effective strategies.MethodsA systematic review and network meta-analysis of randomized controlled trials published up to May 2024 was conducted. Studies assessing acupuncture’s impact on ART outcomes were included. Primary outcomes were clinical pregnancy rate and live birth rate; secondary outcomes included fertilization rate and high-quality embryo rate.ResultsAcupuncture significantly improved clinical pregnancy rate (RR 1.26), live birth rate (RR 1.10), fertilization rate (RR 6.64), and high-quality embryo rate (RR 12.67). Ranking analysis indicated the embryo culture period as the most effective treatment timing, followed by the ovarian stimulation and ART preparation periods. Longer treatment durations (≥3 months) and higher session numbers (≥20) yielded superior outcomes.ConclusionsThese findings underscore the importance of personalized acupuncture protocols to optimize ART success. Tailoring acupuncture protocols based on timing, duration, and frequency may optimize reproductive outcomes in women undergoing ART.